Menstrual management in developmentally delayed adolescent females. (15th March 2017) - Chuah, Irene; McRae, Alexandra; Matthews, Kim; Maguire, Ann M.; Steinbeck, Katharine
Abstract : Background: Requests for assistance in menstrual management and menstrual suppression are a common, emotive and sometimes controversial aspect of adolescent disability care. Aims: To review the uptake and outcomes of menstrual suppression among adolescent patients with developmental delay. Methods: A retrospective review of the medical records of adolescent females with intellectual disability referred for menstrual management to the Paediatric and Adolescent Gynaecology Clinic, Children's Hospital at Westmead, Sydney, for the three‐year period between January 1, 2010 and January 1, 2013. Results: Eighty adolescent patients with developmental delay were identified. A third ( n  = 28) of the patients were pre‐menarcheal at first review with parent/caregivers seeking anticipatory advice. Of the post‐menarcheal patients, the median age of menarche was 12 years (range 10–15 years). First and second line interventions were documented as were reasons for change where applicable. The combined oral contraceptive pill (COCP) was the most frequently used therapy (67%), and 19 patients in total had a levonorgestrel releasing intrauterine system (LNG‐IUS) inserted (31%). Our study population differs from similar previously published groups in the marked absence of the use of depot medroxyprogesterone acetate or the subdermal etonogestrel releasing device. Conclusion: As a paediatrician, it is important to address menstrual management issues and allay caregiver concerns with appropriate advice. Our study supports the use of the COCP as sound first line management in achieving menstrual suppression. The LNG‐IUS appears to be a favourable second line option. Further investigation into longer‐term outcomes and potential complications of device insertion is recommended.